2020
DOI: 10.1111/vox.12935
|View full text |Cite
|
Sign up to set email alerts
|

A novel cancer immunotherapy utilizing autologous tumour tissue

Abstract: Background With the recent interest in personalized medicine for cancer patients and immune therapy, the field of cancer vaccines has been resurrected. Previous autologous, whole cell tumour vaccine trials have not produced convincing results due, in part to poor patient selection and inactivation methos that are harsh on the cells. These methods can alter protein structure and antigenic profiles making vaccine candidates ineffective in stimulating immune response to autochthonous tumour cells. Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Both adjuvants used in this study are known to promote Th1 immune pathway responses. Prior work with vaccine candidates suggested that ADE leading to lung immunopathology might be avoided by using Th1 promoting adjuvants [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both adjuvants used in this study are known to promote Th1 immune pathway responses. Prior work with vaccine candidates suggested that ADE leading to lung immunopathology might be avoided by using Th1 promoting adjuvants [24].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we believe that such a production method could be applied to vaccine candidates targeting other viral, bacterial, and parasitic pathogens. We have already applied such an approach to the generation of solid tumor vaccines and demonstrated their use in both murine and canine disease models [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Blood was collected via cardiac puncture and used fresh for flow analysis. About 50 mg of spleen and tumor tissue were collected and digested into single-cell suspensions as described previously [44]. A small portion of each tumor was formalin-fixed for further histological analyses.…”
Section: Tissue Harvesting and Flow Cytometry Assaysmentioning
confidence: 99%
“…We are developing and have previously reported on the behavior of a new cancer immunotherapy approach for treating solid organ tumors in humans. This method (Innocell™) relies on the use of autologous tumor tissue to provide antigen presentation to the immune system following treatment of the cells with Riboflavin and UV light, which prevents cell replication while maintaining tumor cell metabolic function and phenotypic integrity [ 1 ]. Initial studies in mice demonstrated the ability of this approach to suppress tumor cell growth, generate dendritic and T cell activation, slow metastatic disease progression, and induce production of an immune response in murine tumors for breast cancer when used in combination with adjuvant [ 1 ].…”
Section: Introductionmentioning
confidence: 99%